Proprotein Convertase Subtilisin/Kexin Type 9: From the Discovery to the Development of New Therapies for Cardiovascular Diseases - Nicola Ferri (Scientifica)
The identification of the HMG-CoA reductase inhibitors, statins, has represented a dramatic innovation of the pharmacological modulation of hypercholesterolemia and associated cardiovascular diseases. However, not all patients receiving statins achieve guideline-recommended low density lipoprotein (LDL) cholesterol goals, particularly those at high risk. There remains, therefore, an unmet medical need to develop additional well-tolerated and effective agents to lower LDL cholesterol levels. The discovery of proprotein convertase subtilisin/kexin type 9 (PCSK9), a secretory protein that posttranscriptionally regulates levels of low density lipoprotein receptor (LDLR) by inducing its degradation, has opened a new era of pharmacological modulation of cholesterol homeostasis. This paper summarizes the current knowledge of the basic molecular mechanism underlying the regulatory effect of LDLR expression by PCSK9 obtained from in vitro cell-cultured studies and the analysis of the crystal structure of PCSK9. It also describes the epidemiological and experimental evidences of the regulatory effect of PCSK9 on LDL cholesterol levels and cardiovascular diseases and summarizes the different pharmacological approaches under development for inhibiting PCSK9 expression, processing, and the interaction with LDLR.